Geologi Daerah Likupang Satu dan Sekitarnya Kecamatan Likupang Timur Kabupaten Minahasa Utara Sulawesi Utara - Rumajar, Reyva; Momongan, Andrew (LPPM Universitas PRISMA, 2024)
Administratively, the research area is located in Likupang Satu, Likupang Timur District, North Minahasa Regency, North Sulawesi, with geographical coordinates at UTM zone 51N 728895 – 732851 mT and 180463 – 184492 mU. This study was conducted to understand the geological conditions of the research area, including its geomorphology, stratigraphy, geological structures, and geological history. The research methodology involved several stages: preparation, fieldwork, data processing, and data presentation. The results of the study show that the geomorphology of the research area is divided into five units: Lava Flow Ridge Unit, Pyroclastic Flow Ridge Unit, Lava Flow Plain Unit, Pyroclastic Flow Plain Unit, and Swamp Plain Unit. The stratigraphy of the area consists of four rock units arranged from oldest to youngest: Andesite Lava Igneous Rock Unit, Tuff Unit, Sandstone Unit, and Alluvial Deposit Unit. The geological structure in the area is characterized by jointed faults. The geological history of the area during the Quaternary period indicates that the andesite lava igneous rock was formed from the eruption of an ancient volcano, flowing through the research area. Subsequently, pyroclastic tuff was deposited on top of the lava rock, followed by the deposition of sandstone, and finally, the alluvial deposits have continued to accumulate up to the present day.